The Graduation Program Effects on Armed-Conflict Victims: Results Evaluation from Colombia (2021)
As part of the Colombian government's strategy to support the armed-conflict victims, a Graduation Program called "Transformando Mi Futuro" (Transforming my future) was implemented. Unlike other graduation programs, this one targets the urban population and has no assets transfers. To evaluate this program, a Results Evaluation (Before/After) approach was performed using the information collected before and after implementing the program. The main results show positive changes in well-being and a reduction in the gap between the actual perception of well-being and the expectations for two and five years, and positive changes in labor income and savings. These results suggest that the program contributed to improving the living conditions of participating households. However, heterogeneity analysis shows that impacts are differentiated according initial status of participants. This exercise is part of the set of evaluations carried out within the Platform for Evaluation and Learning of the Graduation Program in Latin America (http://www.plataformagraduacionla.info/)